A simple flash and freeze system for cryogenic time-resolved electron microscopy - Bhattacharjee, Biddut; Rahman, Md Mahfuzur; Hibbs, Ryan E.; Stowell, Michael H. B. (Frontiers in Molecular Biosciences, 2023)
As the resolution revolution in CryoEM expands to encompass all manner of macromolecular complexes, an important new frontier is the implementation of cryogenic time resolved EM (cryoTREM). Biological macromolecular complexes are dynamic systems that undergo conformational changes on timescales from microseconds to minutes. Understanding the dynamic nature of biological changes is critical to understanding function. To realize the full potential of CryoEM, time resolved methods will be integral in coupling static structures to dynamic functions. Here, we present an LED-based photo-flash system as a core part of the sample preparation phase in CryoTREM. The plug-and-play system has a wide range of operational parameters, is low cost and ensures uniform irradiation and minimal heating of the sample prior to plunge freezing. The complete design including electronics and optics, manufacturing, control strategies and operating procedures are discussed for the Thermo Scientific™ Vitrobot and Leica™ EM GP2 plunge freezers. Possible adverse heating effects on the biological sample are also addressed through theoretical as well as experimental studies.